2012
DOI: 10.1093/cid/cis785
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Its Association With Low Bone Mineral Density, HIV-Related Factors, Hospitalization, and Death in a Predominantly Black HIV-Infected Cohort

Abstract: VDD was highly prevalent in black HIV- infected persons but did not explain the observed racial disparity in BMD. Vitamin D deficiency was not more common among HIV- infected persons, nor did it seem associated with HIV- related factors/clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…In HIV, our study is congruent with the study by Sherwood JE, et al which showed that vitamin D deficiency (25(OH)D < 30 ng/dl) was not associated with low BMD in military beneficiaries with HIV[37] and with a study by El-Maouche D, et al which showed that vitamin D deficiency (25(OH)D < 15 ng/dl) was not associated with low BMD in HCV/HIV co-infected adults. [38] Potential explanations include the fact that African American race, which has been shown to effect the relationship between 25(OH)D and BMD,[39, 40] was the most predominant race in this study.…”
Section: Discussionsupporting
confidence: 91%
“…In HIV, our study is congruent with the study by Sherwood JE, et al which showed that vitamin D deficiency (25(OH)D < 30 ng/dl) was not associated with low BMD in military beneficiaries with HIV[37] and with a study by El-Maouche D, et al which showed that vitamin D deficiency (25(OH)D < 15 ng/dl) was not associated with low BMD in HCV/HIV co-infected adults. [38] Potential explanations include the fact that African American race, which has been shown to effect the relationship between 25(OH)D and BMD,[39, 40] was the most predominant race in this study.…”
Section: Discussionsupporting
confidence: 91%
“…An unexpected finding was that women with HIV had higher vitamin D levels than those without HIV infections. Some studies have suggested high rates of vitamin D deficiency among patients with HIV infections patients, whereas others have not . Low levels of vitamin D in individuals with HIV infections can have multiple causes, including the use of antiviral regimens containing ritonavir and efavirenz .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested high rates of vitamin D deficiency among patients with HIV infections patients, whereas others have not. 20,21 Low levels of vitamin D in individuals with HIV infections can have multiple causes, including the use of antiviral regimens containing ritonavir and efavirenz. 22 An explanation for the present findings could be that pregnant women with HIV were particularly careful with their diet and general health care.…”
mentioning
confidence: 99%
“…134 It should be noted that other studies have failed to demonstrate an association between vitamin D level and clinical outcomes. Sherwood and colleagues, 51 in a study involving 271 US participants followed for at least 8 years, failed to show significant association between baseline 25-OHD less than 20 ng/mL and allcause mortality, clinical progression to AIDS, respiratory disease, hospitalizations, and malignancies. However, this study was limited because of its small sample size and modest number of observed clinical outcomes.…”
Section: Hiv Disease Progressionmentioning
confidence: 98%
“…[54][55][56] The level of PTH was also not associated with low BMD in most of these studies. 51,53,55,56 An association between vitamin D and BMD has only been shown by a few investigators. Among 100 HIV-infected women, Dolan and colleagues 57 showed that baseline 25-OHD was positively correlated with higher baseline hip BMD.…”
Section: Osteopenia and Osteoporosismentioning
confidence: 99%